KELIMPAHAN PLANKTON DI DANAU RANO KECAMATAN BALAESANG TANJUNG DAN PENGEMBANGANNYA SEBAGAI MEDIA PEMBELAJARAN - Istadewi, Ika (JSTT, 2016)
This research aims at finding out about the Abundance of plankton development in Rano lake Balaesang Tanjung district as learning media. The research used descriptive qualitative method, population of the research was the whole plankton components in Rano lake. The sample was drawn through purposive sampling with 4 times repetition. The research result reveal that the abundance of plankton consists of 16 spesies the purpose of them 7 class phytoplankton and 3 class of zooplankton. The spesies is Melosira italica, Eucoconeis sp, Opephora martyi, Cyclotella sp, Syendra flugens, Surirella sp, Microcoleus sp, Mougetia viridis, Actinastrum gracillimum, Closterium sp, Hyalosphenia cuneata, Ceratium sp, Cyclops sp, Hyperia sp, Halicyclops sp and Trichocerca iernis. The results also showed Â that the highest abundance of plankton in the morning and in the afternoon is Synedra flugens. Beside, in the day and night the highest abundance is Microcoleus sp. Assessment instructional product of development media video categorized achievement. Therefore, it can be concluded that the abundance of plankton in Rano lake Balaesang Tanjung and its development is viable medium to be aÂ learning is used as a learning source.